Embelin: A novel XIAP inhibitor for the prevention and treatment of chronic diseases. Issue 2 (29th November 2021) - Devi Daimary, Uzini; Girisa, Sosmitha; Parama, Dey; Verma, Elika; Kumar, Aviral; Kunnumakkara, Ajaikumar B.
Abstract: Chronic diseases are a serious health concern worldwide, especially in the elderly population. Most chronic diseases like cancer, cardiovascular ailments, neurodegenerative disorders, and autoimmune diseases are caused due to the abnormal functioning of multiple signaling pathways that give rise to critical anomalies in the body. Although a lot of advanced therapies are available, these have failed to entirely cure the disease due to their less efficacy. Apart from this, they have been shown to manifest disturbing side effects which hamper the patient's quality of life to the extreme. Since the last few decades, extensive studies have been done on natural herbs due to their excellent medicinal benefits. Components present in natural herbs target multiple signaling pathways involved in diseases and therefore hold high potential in the prevention and treatment of various chronic diseases. Embelin, a benzoquinone, is one such agent isolated from Embelia ribes, which has shown excellent biological activities toward several chronic ailments by upregulating a number of antioxidant enzymes (e.g., SOD, CAT, GSH, etc.), inhibiting anti‐apoptotic genes (e.g., TRAIL, XIAP, survivin, etc.), modulating transcription factors (e.g., NF‐κB, STAT3, etc.) blocking inflammatory biomarkers (e.g., NO, IL‐1β, IL‐6, TNF‐α, etc.), monitoring cell cycle synchronizing genes (e.g., p53, cyclins, CDKs, etc.), and so forth. Several preclinical studies have confirmed its excellent therapeutic activities against malicious diseases like cancer, obesity, heart diseases, Alzheimer's, and so forth. This review presents an overview of embelin, its therapeutic prospective, and the molecular targets in different chronic diseases.